Metformin reduces androgen receptor and upregulates homeobox A10 expression in uterine endometrium in women with polycystic ovary syndrome - Miki Ohara; Hiromi Yoshida-Komiya; Miho Ono-Okutsu; Akiko Yamaguchi-Ito; Toshifumi Takahashi; Keiya Fujimori (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) causes anovulation and is associated with a reduced clinical pregnancy rate. Metformin, which is widely used for treating PCOS, can lead to successful pregnancy by restoring the ovulation cycle and possibly improving endometrial abnormality during the implantation period. However, the mechanism by which metformin improves endometrial abnormality remains unknown. Women with PCOS have an aberrant expression of steroid hormone receptors and homeobox A10 (HOXA10), which is essential for embryo implantation in the endometrium. Methods In this study, we examined whether metformin affects androgen receptor (AR) and HOXA10 expression in PCOS endometrium in vivo and in human endometrial cell lines in vitro. Expression of AR and HOXA10 was evaluated by immunohistochemistry, fluorescent immunocytochemistry, and western blot analysis. Results AR expression was localized in both epithelial and stromal cells; however, HOXA10 expression was limited to only stromal cells in this study. In women with PCOS, 3 months after metformin treatment, the expression of AR was reduced in epithelial and stromal cells in comparison to their levels before treatment. In contrast, HOXA10 expression in the stromal cells with metformin treatment increased in comparison to its level before treatment. Further, we showed that metformin counteracted the testosterone-induced AR expression in both Ishikawa cells and human endometrial stromal cells (HESCs); whereas, metformin partly restored the testosterone-reduced HOXA10 expression in HESCs in vitro. Conclusions Our results suggest that metformin may have a direct effect on the abnormal endometrial environment of androgen excess in women with PCOS. Trial registration The study was approved by the Ethical Committee of Fukushima Medical University (approval no. 504, approval date. July 6, 2006), and written informed consent was obtained from all patients. https://www.fmu.ac.jp/univ/sangaku/rinri.html